WhatsINFO: a Gamified Mobile Application Promoting the Integration of Computer Science School Freshmen to the UNLP - Kimura, Isabel (2015)
This paper presents the issue facing university freshmen due to the complexity implied in acquiring new discourses, contents and habits of the institutional culture of which they aim at becoming a part. Online gaming and socializing through digital media are common among young people – they engage their interest and define new ways of expression and communication. Ubiquity is another requirement of the new generations, with smartphones being the most chosen mobile devices for communication and socialization. In this context, we present the WhatsINFO mobile application, whose goal is to mitigate the divide existing between new students and university culture through a technological tool that is close to teenage culture. WhatsINFO is a gamified mobile application that accompanies and encourages communication and participation of National University of La Plata (UNLP) Computer Science School freshmen during their entry course. WhatsINFO was tested during the 2014 entry course of the Computer Science School of the UNLP with over a hundred students. This field test yielded encouraging results regarding its incorporation as a complementary device promoting a new learning space.